SATURNE: a distributed computing system which tolerates faults and intrusions - Deswarte, Y.; Fabre, J.-C.; Fray, J.-M.; Powell, D.; Ranea, P.-G. (Workshop on the Future Trends of Distributed Computing Systems in the 1990s: Proceedings, 1988)
SATURNE, a research project aimed at increasing distributed system reliability by means of fault-tolerance and security by means intrusion tolerance, is discussed. The saturation and fragmentation-and-scattering techniques proposed by the SATURNE project show that it is possible to exploit more distribution than has been done up to now, in order to increase computing system dependability, and more precisely reliability with respect to accidental, physical faults, and security with respect to intrusions, i.e. deliberate, human-made, interaction faults.< >